Study on a compact and adaptable Thomson Spectrometer for laser-initiated 11B(p, α)8Be reactions and low-medium energy particle detection. (11th May 2016) - Consoli, F.; Angelis, R. De; Bonasera, A.; Sura, J.; Andreoli, P.; Cristofari, G.; Cipriani, M.; Giorgio, G. Di; Ingenito, F.; Barbarino, M.; Labaune, C.; Baccou, C.; et al.
Abstract: Thomson Spectrometers are of primary importance in the discrimination of particles produced by laser-plasma interaction, according to their energy and charge-mass ratio. We describe here a detailed study on a set of Thomson Spectrometers, adaptable to different experimental situations, with the aim of being placed directly within the experimental chamber, rather than in additional extensions, in order to increase the solid angle of observation. These instruments are suitable for detection of low-medium energy particles and can be effectively employed in laser-plasma experiments of 11 B ( p, α) 8 Be fusion. They are provided with permanent magnets, have small dimensions and compact design. In these small configurations electric and magnetic fringing fields play a primary role for particle deflection, and their accurate characterization is required. It was accomplished by means of COMSOL electromagnetic solver coupled to an effective analytical model, very suitable for practical use of the spectrometers. Data from experimental measurements of the magnetic fields have been also used. We describe the application of the spectrometers to an experiment of laser-plasma interaction, coupled to Imaging Plate detectors. Data analysis for spectrum and yield of the detected radiation is discussed in detail.